Oil Film Dynamics in Aero Engine Bearing Chambers : Fundamental Investigations and Numerical Modelling. - Hashmi, Amir A. (Forschungsberichte Aus Dem Institut Für Thermische Strömungsmaschinen Ser., 2012)
Annotation